Two-year clinical evaluation of lithia-disilicate-based all-ceramic crowns and fixed partial dentures - (:unkn) unknown (ELSEVIER SCI LTD, 2006)
Objectives. The aim of this study was to evaluate the clinical performance of crowns and fixed partial dentures (FPDs) made with the Empress 2 system over a 2-year period. Methods. Twenty anterior or posterior all-ceramic (Empress 2) crowns and 20 anterior or posterior, three-unit fixed partial dentures were fabricated for 15 patients. Evaluations of the restorations were performed at baseline and once a year during the 2-year follow-up period. U.S. Public Health Service criteria were used to examine the marginal adaptation, color match, secondary caries and visible fractures in the restorations. Survival rate of the restorations were determined using Kaplan-Meier statistical analysis. Results. U.S. Public Health Service criteria showed 100% Alpha scores concerning recurrent caries for both crowns and FPDs. No crown fractures were observed during the 2-year follow-up, however, 10 (50%) catastrophic failures of FPDs occurred. Five (25%) failures occurred within the 1-year clinical period and the others (25%) within the second year. Significance. Single unit Empress 2 all-ceramic crowns exhibited a satisfactory clinical performance over 2-year period. Furthermore, the high fracture rate of Empress 2 FPDs limits the usage of Empress 2 for the fabrication of all-ceramic FPD. (C) 2005 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: dental ceramic; clinical evaluation; failure of fixed partial dentures; STRENGTH; METAANALYSIS; LAYER